Trans fatty acid accumulation in the human placenta. (7th February 2017) - Wada, Yoshiro; Yoshida‐Yamamoto, Shumi; Wada, Yoshinao; Nakayama, Masahiro; Mitsuda, Nobuaki; Kitajima, Hiroyuki
Abstract : Trans fatty acid may impair fetal growth and infant neurodevelopment, but the quantity in a placenta and human tissues remains unknown. To address the issue, a simple and reliable method of quantification is needed. We established a method of quantifying trans‐octadecenoic acids (trans‐6, 8, 9, 11 18:1 fatty acids, TOAs), a major component of trans fatty acid, in human tissue samples, and then determined the TOAs level in the placenta. Oleic acid (OA) (C18:1(9c)) was measured by isotope dilution gas chromatography–mass spectrometry, and the TOAs level was subsequently calculated based on the ratio of the peak areas for TOAs and OA (TOAs/OA) in the mass chromatogram. Lipids were extracted from 28 human placentas at different gestational ages from 28 to 41 weeks, and the TOAs and OA levels were measured. In method validation, the limit of detection for elaidic acid (trans‐9, 18:1 fatty acid), a major component of TOAs, was 0.57 ng, and linearity of calibration ranging from 7.7 to 68.0 μg/g placenta for TOAs. In human placenta analysis, the TOAs level was significantly higher in term ( n  = 15, 40.2 ± 9.7 μg/g placenta) than in preterm placentas ( n  = 13, 18.9 ± 7.4 μg/g placenta) ( p  < 0.001), while OA levels were similar in term ( n  = 15, 863 ± 132 μg/g placenta) and preterm ( n  = 13, 743 ± 283 μg/g placenta) placentas ( p  = 0.15). TOAs accumulate in the placenta as pregnancy progresses and have a fate different from that of OA in vivo. To our knowledge, this is the first report of TOA quantification in human tissue samples. Copyright © 2017 John Wiley & Sons, Ltd.